Analisis Kesempatan Kerja Yang Dibutuhkan dalam Perekrutan Karyawan di Batam yang Menggunakan Iklan Lowongan Pekerjaan di Media Koran Batam Pos dan Tribun Batam - Dina Hidayani; Dwi Kartikasari (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2016)
This research aimed to analyze the problem of equal employment opportunity based on gender and level of education and level of work and the majors are required. This research is an explanatory research. The subject of this research is a newspaper that published a job ad in the year 2015-2016. Purposive sampling technique is used by the researcher to obtain the sample. Data analyses used is descriptive analysis. The result showed that in 66% of them include gender as one of the required qualifications. 40% male, 60% female. In this research missed the fact that job advertisements in Batam tends to favor a particular gender. For the characteristics of the level of work required for a particular gender, were classified as medium there are 55% and 61% is low gender to female. And for courses that required accounting majors there are 54% female. The next research there are 74% include the level of education as one of the required qualifications. In this research missed the fact that job advertisements in Batam tends to favor a certain level of education. For the characteristics of the level of work required for a certain level of education, which is classified as medium there are 45% D3 and 89% senior high school relatively low. And for the department there are 16% of the required accounting majors at the level of senior high school.